Calidad del servicio y satisfacción del cliente externo de Loreto Distribuciones SAC Iquitos diciembre 2020 - Reyes Flores, Yelsent Anyel Marina (2022)
The main objective of the research work Quality of Service and External Customer Satisfaction of Loreto Distributions SAC Iquitos, December 2020, was to determine the relationship between the Quality of Service and the Satisfaction of external customers of Loreto Distributions SAC, Iquitos, 2020, is descriptive level with a quantitative approach and a non-experimental design with a cross-sectional or transactional section, the sample consisted of 110 main clients, the results show that three dimensions of service quality: tangible elements, reliability and empathy are related to client satisfaction , while the dimensions of responsiveness and security are not correlated with customer satisfaction. In conclusive terms, there is a correlation between the variables quality of service and customer satisfaction at Loreto Distributions SAC.